2012
DOI: 10.1051/0004-6361/201118002
|View full text |Cite
|
Sign up to set email alerts
|

3D simulations of Betelgeuse’s bow shock

Abstract: Betelgeuse, the bright, cool red supergiant in Orion, is moving supersonically relative to the local interstellar medium. The star emits a powerful stellar wind that collides with this medium, forming a cometary structure, a bow shock, pointing in the direction of motion. We present the first 3D hydrodynamic simulations of the formation and evolution of Betelgeuse's bow shock. The models include realistic low-temperature cooling and cover a range of plausible interstellar medium densities of 0.3-1.9 cm −3 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 52 publications
4
68
2
Order By: Relevance
“…As a result, the Kelvin-Helmholtz instabilities are much greater, leading to a large-scale instability that changes the shape of the entire bow shock. This is contrary to the results of Mohamed et al (2012), who obtained a smooth bow shock for similar input parameters. This difference may be the result of a different numerical treatment (grid versus SPH), but may also result from the total timescale of the Fig.…”
Section: Warm Ambient Mediumcontrasting
confidence: 99%
See 2 more Smart Citations
“…As a result, the Kelvin-Helmholtz instabilities are much greater, leading to a large-scale instability that changes the shape of the entire bow shock. This is contrary to the results of Mohamed et al (2012), who obtained a smooth bow shock for similar input parameters. This difference may be the result of a different numerical treatment (grid versus SPH), but may also result from the total timescale of the Fig.…”
Section: Warm Ambient Mediumcontrasting
confidence: 99%
“…4.2.1 yield a mass in the arcs of ∼0.1 M (including 90% CSM and 10% ISM material). According to Mohamed et al (2012), the observed low mass in the arcs might indicate that the bow shock created by the RSG wind has a very young age, of the order of 20 000 yrs, and may not yet have reached a steady state. But, the existence of (non-homogeneous) clumps in the inner wind travelling all the way to the bow shock region might also explain the low mass in the arcs as derived from the Herschel images.…”
Section: Mass Of the Arcs And Linear Barmentioning
confidence: 99%
See 1 more Smart Citation
“…At these phases, massive stars may undergo rapid transitions from red to blue supergiants and vice versa in the Hertzprung-Russell diagram, and the stellar wind velocities also change rapidly. Mohamed et al (2012) found that the bow shock formed by Betelgeuse is still young (<30 kyr). The total kinetic power is rather low, but the star is relatively close and a possible low X-ray luminosity can still be detectable.…”
Section: Betelgeusementioning
confidence: 98%
“…Subsequent attempts by van Marle et al (2011) and Decin et al (2012) to model the bow shock of α-Orionis showed large instabilities that would be observable with Herschel, if they exist. The absence of instabilities has been explained by Mohamed et al (2012) and Appendix A and associated movies are available in electronic form at http://www.aanda.org Mackey et al (2012) as evidence that the bow shock is still in an early stage of formation and that the instabilities have not yet had time to develop.…”
Section: Introductionmentioning
confidence: 99%